An herbal medicine, Go-sha-jinki-gan (GJG), increases muscle weight in severe muscle dystrophy model mice. (December 2017) - Takemoto, Yusei; Inaba, Shoya; Zhang, Lidan; Baba, Kousuke; Hagihara, Keisuke; Fukada, So-ichiro
Summary: Go-sha-jinki-gan (GJG), a traditional Japanese herbal medicine has a clinical implication to alleviate age-related symptoms, especially in some motor disorders. However, the scientific evidence is limited, and there is a possibility to expand the medical application range of GJG. Using senescence-accelerated mice, our group showed that GJG exerted an effect to prevent sarcopenia, the aged-related loss of skeletal muscle. Because muscular dystrophy is characterized by a progressive loss of skeletal muscle, we examined the effects of GJG on a mouse model of muscular dystrophy. Using a newly established mouse model for Duchenne muscular dystrophy (DMD), DBA/2- mdx, we showed that GJG significantly increased the body and skeletal muscle weights in comparison to the control DBA/2- mdx mice, regardless of gender. The increased skeletal muscle mass resulted from an increment in the myofiber size, but not from the myofiber number. Both the skeletal muscle regenerative ability and the accumulation of fibrosis (the dystrophic pathology) in GJG-fed DBA/2- mdx mice were comparable to those in control DBA/2- mdx mice, suggesting that the cellular target of GJG is myofibers, with no contribution from the muscle satellite cells neither in an direct nor in an indirect manner. Taken together, GJG increased the skeletal muscle mass in a mouse model of muscular dystrophy, in addition to our previously tested sarcopenia mouse model. Highlights: GJG significantly increased the body and muscle weight of DBA/2- mdx regardless of gender. GJG significantly increased myofiber size but not myofiber number. GJG did not affect muscle regeneration or pathological feature of DBA/2- mdx .